Academic fraudulence in online degrees and exams at Australian universities - E, Smith; L, Clarke,; P, Carmona,; S, Cerimagic, (IJRDO- Journal of Educational Research, 2017)
In recent years an ever increasing number of universities have started to offer online degrees. In Australia most universities offer online degrees, there however currently there is one leading online higher education provider, which this study will be referred to as ‘online degree providers’ (ODP). Along with this new method of completing degrees comes new forms of academic dishonesty and misconduct. Academic dishonesty and misconduct among students is not a new phenomenon. Brimble and Stevenson-Clarke (2006) find that not only is academic dishonesty widespread, it is also often underestimated by universities. Additionally, researchers have found that technology has enabled students to cheat in a number of different ways (Etter et al., 2006; Devlin and Gray, 2007; Howard and Davies, 2009). For example, students now can access information online via their phones while sitting in a closed-book exam (Kuntz Butler, 2014). This paper contributes to the limited research literature on academic dishonesty and misconduct in online programs and online exams at Australian universities by taking a close look at what academic dishonesty and misconduct is and how it is happening. It is important that these questions be understood because, students who cheat at university are more likely to become professionals who in the future will engage in illegal, unethical or immoral behaviours in the workplace. Even though this paper considers academic dishonesty broadly, the focus of the paper is on cheating in online exams.